2019
DOI: 10.1177/2473011419s00154
|View full text |Cite
|
Sign up to set email alerts
|

First Tarsometatarsal Fusion Using Saw Preparation vs. Standard Preparation of the Joint: A Cadaver Study

Abstract: Category: Basic Sciences/Biologics, Midfoot/Forefoot Introduction/Purpose: First tarsometatarsal (TMT) joint fusion is indicated for several underlying causes of first ray dysfunction and pain, including arthritis, traumatic injury, and recurrent hallux valgus. Preparation of the joint surface by denuding the articular cartilage is a key step for arthrodesis, as inadequate preparation may result in poor fixation and non-union. However, excessive removal of cartilage and bone may result in excessive shortening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Despite these findings, only one patient (from the 32 sampled) had symptoms of transfer metatarsalgia (20) . Dahlgren et al showed in cadavers a mean metatarsalcuneiform length decrease of 3mm when using osteotomes in comparison to a mean of 6.9mm when the saw was used to prepare the site (36) . Plantarflexion of the first ray is also challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these findings, only one patient (from the 32 sampled) had symptoms of transfer metatarsalgia (20) . Dahlgren et al showed in cadavers a mean metatarsalcuneiform length decrease of 3mm when using osteotomes in comparison to a mean of 6.9mm when the saw was used to prepare the site (36) . Plantarflexion of the first ray is also challenging.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,10,14,25,33 Literature review of shortening by curettage techniques range from 0.86 to 5.0 mm. 3,10,25,35 One can easily see the variances in technique and subsequent end results. The reported shortening in AP radiographs of 3.1 mm (95% CI 2.4-3.7) of bone segment length loss for first TMT fusion was consistent in our study and on the low end of that reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,10,13,25 Currently, there is a perception that manual joint preparation by curettage may be a more appropriate method to reduce shortening and complications. 3,10,25,35 This perception may be inaccurate, as it has been found that the range of shortening using this technique ranges from 0.86 to 5.0 mm. 3,10,25,35 Additionally, there are other issues of curettage technique that may play a role in the incidence of nonunions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations